Setting targets for human resources for eye health in sub-Saharan Africa: what evidence should be used?. Issue 1 (December 2016) - Courtright, Paul; Mathenge, Wanjiku; Kello, Amir; Cook, Colin; Kalua, Khumbo; Lewallen, Susan
Abstract With a global target set at reducing vision loss by 25% by the year 2019, sub-Saharan Africa with an estimated 4.8 million blind persons will require human resources for eye health (HReH) that need to be available, appropriately skilled, supported, and productive. Targets for HReH are useful for planning, monitoring, and resource mobilization, but they need to be updated and informed by evidence of effectiveness and efficiency. Supporting evidence should take into consideration (1) ever-changing disease-specific issues including the epidemiology, the complexity of diagnosis and treatment, and the technology needed for diagnosis and treatment of each condition; (2) the changing demands for vision-related services of an increasingly urbanized population; and (3) interconnected health system issues that affect productivity and quality. The existing targets for HReH and some of the existing strategies such as task shifting of cataract surgery and trichiasis surgery, as well as the scope of eye care interventions for primary eye care workers, will need to be re-evaluated and re-defined against such evidence or supported by new evidence.